(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Relevance. Numerous scientific studies have noted unfavorable dynamics in the health of preschool children (Yurko G.P., 2000; Maimulov V.G. et al ., 2003; Rapoport I.K. et al ., 2004; Simonova I.V., 2006). Currently, no more than 10% of senior preschool children can be considered absolutely healthy. Almost 60% of children are revealed chronic diseases .Frequent illnesses in children are not only a medical problem, but also have serious social and economic consequences. It has been shown that frequent illnesses can lead to social maladjustment of the child due to limited opportunities for communication with peers.